Harvesting hope : the story of Cesar Chavez - Krull, Kathleen. (Harcourt, inc., 2003)
A biography of Cesar Chavez, from age ten when he and his family lived happily on their Arizona ranch, to age thirty-eight when he led a peaceful protest against California migrant workers' miserable working conditions.